British torture in the 'war on terror'. (June 2017) - Blakeley, Ruth; Raphael, Sam
Despite long-standing allegations of UK involvement in prisoner abuse during counterterrorism operations as part of the US-led 'war on terror', a consistent narrative emanating from British government officials is that Britain neither uses, condones nor facilitates torture or other cruel, inhuman or degrading treatment and punishment. We argue that such denials are untenable. We have established beyond reasonable doubt that Britain has been deeply involved in post-9/11 prisoner abuse, and we can now provide the most detailed account to date of the depth of this involvement. We argue that it is possible to identify a peculiarly British approach to torture in the 'war on terror', which is particularly well-suited to sustaining a narrative of denial. To explain the nature of UK involvement, we argue that it can be best understood within the context of how law and sovereign power have come to operate during the 'war on terror'. We turn here to the work of Judith Butler, and explore the role of Britain as a 'petty sovereign', operating under the state of exception established by the US executive. UK authorities have not themselves suspended the rule of law so overtly; indeed, they have repeatedly insisted on their commitment to it. Nevertheless, they have been able to construct a rhetorical, legal and policy 'scaffold' that has enabled them to demonstrate at least procedural adherence to human rights norms while, at the same time, allowing UK officials to acquiesce in the arbitrary exercise of sovereignty over individuals who are denied any access to appropriate representation or redress in compliance with the rule of law.